Photochemical Behavior of Multicomponent Polymeric-based Materials - Rosu, Dan.; Visakh P. M.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book offers in-depth insights into the photochemical behavior of multicomponent polymeric-based materials, with a particular emphasis on the photodegradation and photostabilization of these materials. Studying various classes of materials bases such as polysaccharides, wood, synthetic polymers, rubber blends, and nanocomposites, it offers a valuable reference source for graduate and postgraduate students, engineering students, research scholars and polymer engineers working in industry.
From the Contents: Theoretical aspects regarding polymer photochemistry -- Factors influencing the photochemical behavior of multicomponent polymeric materials -- Polymer materials: photodegradation mechanism.
Keywords: Ceramic materials; Polymers; Mechanics, Applied; Solids; Ceramics; Polymers; Solid Mechanics